Effect of polymorphisms in CYP3A4, PPARA, NR1I2, NFKB1, ABCG2 and SLCO1B1 on the pharmacokinetics of lovastatin in healthy Chinese volunteers. (January 2017) - Zhao, Guilian; Liu, Mei; Wu, Xiujun; Li, Guofei; Qiu, Feng; Gu, Jingkai; Zhao, Limei
Aim: This study examined whether gene polymorphisms ( CYP3A4, ABCG2, SLCO1B1, NR1I2, PPARA and NFKB1 ) influenced the pharmacokinetics of lovastatin in Chinese healthy subjects.Patients & method: Plasma concentrations of lovastatin and lovastatin acid were quantified using LC/MS/MS.Results: PPARA c.208+3819 G allele carriers had approximately twofold higher AUC0-∞ and Cmax of lovastatin than wild-type ( PPARA c.208+3819 AA) subjects. After adjustment for the PPARA variants, subjects with the SLCO1B1 521TT genotype had approximately 50% lower AUC0-∞ of lovastatin acid than those with 521TC/CC genotypes, while the AUC0-∞ of lovastatin lactone in NFKB1 -94 DD wild-type carriers was twofold higher than in mutant homozygotes carriers.Conclusion: Gene polymorphisms of PPARA, SLCO1B1 and NFKB1 affected the pharmacokinetics of lovastatin.